The media training bible : 101 things you absolutely, positively need to know before your next interview - Phillips, Brad, ....- (Washington : SpeakGood press, 2013)
Delivering an effective media interview is more challenging than ever before. Today's media spokesperson must compete with shrinking audience attention spans, cope with social media overload, and confront sensationalized reporting. Given those challenges, how can you create positive messages that cut through the noise and motivate your audiences? How can you respond to difficult questions in a confident manner that increases your credibility? And how can you navigate your company through a media crisis so it becomes a mere blip instead of a reputation-destroying disaster? Brad Phillips, one of the world's top media trainers, will lead you through an engaging mix of 101 two-page lessons, three dozen real-life case studies, and several hands-on exercises. He will teach you how to become an effective media spokesperson, eliminate your fear, build your brand, and enhance your reputation.
Keywords: Interviews; Mediatraining